Mysteries of Magnetic Monopoles in the Universe - Jeong, Eue-Jin; Edmondson, Dennis (European Journal of Applied Sciences, 2025)
Charge conservation in the theory of elementary particle physics is one of the best-established principles in physics. As such, if there are magnetic monopoles in the universe, magnetic charge will most likely be a conserved quantity like electric charges. If neutrinos are magnetic monopoles, as physicists have reported the possibility, the Earth should show signs of having magnetic monopole charge on a macroscopic scale since neutrons must also have magnetic monopole charge if general charge conservation principle is valid. To test this hypothesis, experiments were performed to detect the collective effect of magnetic monopole charge of neutrons on the earth’s equator using two balanced high strength neodymium rod magnets. We were able to identify non-zero magnetic monopole charge of the individual neutrons from the experiments. The presence of individual magnetic monopole charges in the universe prompted proposition of the new symmetric form of Maxwell’s equations. Based on the theoretical investigation of the new Maxwell’s equations, we conclude that magnetic monopole neutrinos are the cause of the origin of quantum mechanical uncertainty, dark energy and the medium for electromagnetic wave propagation in space.